Strategi Komunikasi Digital Media Sosial sebagai Media Promosi dan New Branding (Studi Kasus Media Sosial Om Moes) - Zaki Muhamad Dani; Gregorius Genep Sukendro (Kiwari, 2023)
Social media is a medium that is used to build a self-representation of a company or individual, social media can be used to do digital marketing or digital marketing. Digital marketing is a marketing activity or promotion of a brand or product, using digital media or the internet. The goal is to attract potential customers broadly, quickly and precisely. This was also carried out by Om Moes' social media to promote the Moestopo Faculty of Communication Sciences to the public. Dr. Moestopo. Previously, the Moestopo Faculty of Communication Sciences had a social media account, but this social media was considered ineffective because the content was monotonous and too formal. This study uses a type of qualitative research that is useful for providing facts and data regarding Om Moes' Digital Social Media Communication Strategy as a Promotional Media and New Branding for the Moestopo Faculty of Communication Sciences. The results of this study are social media Om Moes conducting digital marketing through social media Instagram with content that contains information on the representation of Moestopo Faculty of Communication Sciences students because this is considered appropriate considering the target is young people. Media sosial merupakan media yang digunakan dalam membangun representasi diri sebuah perusahaan maupun individu, Media sosial dapat digunakan untuk digital marketing atau pemasaran digital. Digital marketing adalah tindakan memasarkan atau mempromosikan brand atau produk melalui media digital atau internet. Tujuannya adalah untuk menarik pelanggan potensial secara luas, cepat dan akurat. Hal ini pula yang dilakukan oleh media sosial Om Moes untuk mempromosikan Fakultas Ilmu Kominunikasi Moestopo kepada masyarakat, Om Moes merupakan akun media sosial yang didirikan dibawah naungan Fakultas Ilmu Kominunikasi Universitas Prof. Dr. Moestopo. Fakultas Ilmu Kominunikasi Moestopo sebelumnya mempunyai akun media sosial, namun media sosial tersebut dianggap tidak efektif karena isi konten yang monoton dan terlalu formal. penelitian ini menggunakan jenis penelitian kualitatif yang berguna untuk memberikan fakta dan data mengenai Strategi Komunikasi Digital Media Sosial Om Moes Sebagai Media Promosi Dan New Branding Fakultas Ilmu Kominunikasi Moestopo. Hasil dari penelitian ini adalah media sosial Om Moes melakukan pemasaran digital melalui media sosial Instagram dengan konten yang berisi informasi representasi mahasiswa Fakultas Ilmu Kominunikasi Moestopo karena hal ini dianggap tepat mengingat target yang merupakan anak muda.